Evaluation of Four Soybean Varieties Resistance Against Soybean Cyst Nematode (Heterodera glycines) in Greenhouse Condition - S. Rezaei2, S. Shahabi1*, A. Kheiri2 and (Journal of Phytology, 2010)
In this study, during the years 2005-2006, 70 soil and infected root samples were collected from different regions in Golestan province. Nematodes were extracted from soil and root samples followed by mounting in glycerin. Microscopic slides were prepared and morphological as well as morphometric characteristics were studied using light microscope. Four commonly soybean varieties including Sahar, DPXï€„ Gorgan-3 and Wiliames used for observation synchytia as well as comparison their susceptibility. For this purpose, soybean seedlings were artificially inoculated with 4000 eggs and larvae which obtained from collected cysts on soybean seedlings per pot. The total number of cysts produced in infected roots of four soybean varieties was recorded after 4 month. Resistance of varieties against Heterodera glycines was also measured by average length and width of synchytia and nematode reproduction rate. There are no cysts on DPX variety while four cysts in Saharï€„ eight in Gorgan-3 and 15 cysts on Wiliames could be observed. Also, results showed that the most sensitive varieties were Wiliames, Gorgan-3 and Sahar, respectively and DPX is diagnosed as resistant one.